CLIL APPROACH IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Content and Language Integrated Learning (CLIL) has become an innovative and effective approach in teaching English as a Foreign Language (EFL). It integrates subject content and language learning, enabling students to acquire linguistic competence while simultaneously developing subject knowledge. This article explores the theoretical foundations, pedagogical principles, and practical implications of CLIL in primary and secondary education. Drawing on the framework proposed by Do Coyle and supported by the educational principles of David Marsh, the study examines how CLIL enhances communicative competence, cognitive development, and learner motivation. The findings indicate that the CLIL approach significantly improves students’ language proficiency, critical thinking skills, and intercultural awareness. The paper concludes that CLIL represents a transformative methodology in modern EFL classrooms.